DETERMINAN PEMANFAATAN POS KESEHATAN DESA (POSKESDES) PADA KELUARGA - Zuhrina Zuhrina Aidha (Communication and Social Dinamics (CSD), 2016)
Poskesdes (Rural Health Care) is a Community-Based Health Effort established to optimalize the potentials existing in the community to improve the health status and the utilization of health services. The purpose of this quantitative study was to analyze the utilization determinant of rural health post by the families in Kutalimbaru Subdistrict, Deli Serdang District. The data for this study were obtained through questionnaire-based interview with 80 respondents comprising the mothers with babies/children under five years old.The data obtained were analyzed through path analysis method. The result of this study showed that 50% of the respondents were of 20-30 years old and 28.8% had negative relationship with the utilization (-0.288). Majority of the respondents (48.7%) were SMA (High School) graduates and 18.6% had relationship with the utilization (0.186). The knowledge of the respondents (85%) about Poskesdes was good and 22.2% had relationship with the utilization (0.222). The attitude of the respondents (67.5%) towards Poskesdes was good and 49.4% had relationship with the utilization (0.494). 55% of the respondents had high income and 27% had negative relationship with the utilization (-0.270). 62.5% of the respondents had poor family support in utilizing the Poskesdes and 26.6% had negative relationship with the utilization (-0.266). The houses of the majority (55%) of the respondents were not far from the Poskesdes and 24.6% had relationship with the utilization of Poskesdes (0.246). 66.3% of the respondents had a high need to the Poskesdes and 4% had relationship with the utilization of Poskesdes (0.040). It is suggested to improve the role of community members in health activities and the provision of information that the community members would prefer visiting the Poskesdes to have their health checked, to provide more extension and to hold more meetings with the community members that the community members are willing to optimalize the utilization of Poskesdes. Keywords: Utilization, Poskesdes, Utilization Determinant, Community-Based Health Effort